Factor Analysis of Teachers' Skills in Directing Silent Sitting in View of Emotion Regulation and Concentration of Early Childhood Children - Pujiarto; Dwi Yuniati Ningsih (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
This study aims to investigate the effect of teachers' ability to direct sitting still on early childhood emotion regulation and concentration. Education plays a crucial role in changing bad habits into good ones, shaping students' morals, character and intelligence to achieve superior learning achievements and compete. In the context of education, silent sitting can help students develop better focus and concentration skills, and reduce anxiety and stress. This research method uses the Partial Least Square (PLS) approach using Smart PLS 3.0 software. PLS is a variant-based method of Structural Equation Modeling (SEM) aiming to analyze the relationship between variables. The results showed that the teacher's ability to direct sitting still positively and significantly affects Emotion Regulation and Concentration in early childhood. These results highlight the importance of the teacher's role in creating a learning environment conducive to developing emotions and concentration in early childhood. This study implies the need to develop teaching skills for teachers to implement various learning strategies effectively and efficiently.